2021
DOI: 10.3390/cancers13123093
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β and Oxidative Stress in Cancer: A Crosstalk in Driving Tumor Transformation

Abstract: Cancer metabolism involves different changes at a cellular level, and altered metabolic pathways have been demonstrated to be heavily involved in tumorigenesis and invasiveness. A crucial role for oxidative stress in cancer initiation and progression has been demonstrated; redox imbalance, due to aberrant reactive oxygen species (ROS) production or deregulated efficacy of antioxidant systems (superoxide dismutase, catalase, GSH), contributes to tumor initiation and progression of several types of cancer. ROS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The redox imbalance, often arises from aberrant accumulation of ROS and is marked by oxidative stress, can promote progression of multiple diseases ( Sies et al, 2017 ). The crosstalk between redox metabolism and TGF-β signaling during cancer and fibrosis is comprehensively reviewed elsewhere ( Richter et al, 2015 ; Ramundo et al, 2021 ). Noteworthy, the enzyme NADPH oxidase 4 (NOX4) appears to play a main role in mediating TGF-β-induced ROS generation under many circumstances ( Cucoranu et al, 2005 ; Sturrock et al, 2006 ; Carmona-Cuenca et al, 2008 ; Michaeloudes et al, 2011 ; Boudreau et al, 2012 ).…”
Section: Tgf-β Signaling and Other Aspects Of Cell Metabolismmentioning
confidence: 99%
“…The redox imbalance, often arises from aberrant accumulation of ROS and is marked by oxidative stress, can promote progression of multiple diseases ( Sies et al, 2017 ). The crosstalk between redox metabolism and TGF-β signaling during cancer and fibrosis is comprehensively reviewed elsewhere ( Richter et al, 2015 ; Ramundo et al, 2021 ). Noteworthy, the enzyme NADPH oxidase 4 (NOX4) appears to play a main role in mediating TGF-β-induced ROS generation under many circumstances ( Cucoranu et al, 2005 ; Sturrock et al, 2006 ; Carmona-Cuenca et al, 2008 ; Michaeloudes et al, 2011 ; Boudreau et al, 2012 ).…”
Section: Tgf-β Signaling and Other Aspects Of Cell Metabolismmentioning
confidence: 99%
“…Similar to the role of oxidative stress in Parkinson’s disease, a role of reactive oxygen species in the pathogenesis of renal fibrosis has been established ( 6 , 50 , 95 , 96 ). In fact, TGFβ has been shown to increase reactive oxygen species due to increased expression of NADPH oxidases especially Nox4 that contribute to the expression of fibrotic markers ( 24 , 27 , 97 , 98 ). Along with quenching reactive oxygen species in neuronal cells in Parkinson’s disease, DJ-1 has been shown to regulate proliferation of cancer cells including breast, lung, thyroid, pancreas, and prostate among many ( 60 , 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that TGF-β regulates the production of reactive oxygen species (ROS) or modulates antioxidant systems and redox-sensitive transcription factors in cancer cell metabolism by increasing the redox imbalance. Moreover, increased ROS production may directly induce TGF-β expression at a nuclear level (Ramundo et al, 2021). Kumari et al (2021) also reported that oxidative stress and hypoxia lead to the accumulation of misfolded proteins in the endoplasmic reticulum (ER), thus inducing ER stress (ERS), which is modulated by G protein-coupled receptors (GPCRs) via ERS sensors, to support cancer cell survival and inhibit cell death.…”
Section: Tgf-βmentioning
confidence: 99%